Measuring Clothing Color and Design Symbolism Preferences and Purchase Intentions of Asian Indian Females at Different Levels of Acculturation. (18th July 2013) - Presley, Ann Beth; Campassi, Whitney Upchurch
Abstract : The purpose of this study was to develop a reliable and valid instrument to measure color, design clothing preferences, and purchase intentions of Asian-Indian female consumers; secondarily, to determine if westernized clothes with Asian-Indian ethnic dress elements might be purchased more often than westernized clothing with design attributes primarily symbolic of American culture at different levels of acculturation. The instrument included a modified acculturation scale, limited demographics, and the developed Clothing Preferences and Purchase Intention Instrument. The instrument consisted of four components: Color Symbolism and Purchase Intention, Design Symbolism and Purchase Intention, Symbolic Attributes Scale, and Clothing Preference and Purchase Intention for Mainstream American versus Asian-Indian Inspired. All of the scales had high reliability. Of the 30 colors in the instrument, red, magenta, orange gold, yellow, cobalt blue, and purple were symbolic of Asian-Indian dress; hunter green, navy blue, baby blue, and blue were considered western colors. Neutral colors were eliminated. Nine of the 27 tunics in the instrument were highly indicative of Asian-Indian clothing; 11 were indicative of westernized clothing. Secondarily, Asian-Indians preferred and showed intent to purchase westernized clothing with colors and designs associated with their native country's traditional dress regardless of acculturation.